Digital Literacy Training for Muslim Community Leaders in Klaten Utara, Indonesia to Enhance Da'wah Communication - Shafa Alistiana Irbathy; Moh. Amiril Mukminin; Naomi Fahma; Tri Wahyudi Ramdhan (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This community service aimed to enhance the digital literacy of Muslim community leaders (Takmir Masjid) in Klaten Utara, Indonesia, to improve the effectiveness of da'wah communication. The training program focused on equipping participants with the knowledge and skills to utilize digital platforms for religious outreach. The program covered various topics, including creating engaging content, utilizing social media effectively, and understanding digital ethics. Participants learned to create informative and engaging da'wah content by utilizing various digital platforms and multimedia tools. The training employed a participatory approach, involving lectures, discussions, and practical exercises. A total of 30 Takmir Masjid from 30 mosques participated in the program. The results showed a significant improvement in participants' understanding and skills in using digital media for da'wah purposes. This program is expected to contribute to the development of more effective and engaging da'wah communication in the digital age, fostering a broader reach and deeper understanding of Islamic teachings within the community.